CHORD LENGTH DISTRIBUTION FUNCTION FOR LENS - Harutyunyan, H.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In the paper a formula for the chord length distribution function of a lens is obtained. In the special case of a regular lens the table of values of the chord length distribution function is given.
Keywords: chord length distribution function; regular lens